1993
DOI: 10.1002/zoo.1430120204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of urinary immunoreactive steroid metabolites and gonadotropins for characterization of the estrous cycle, breeding period, and seasonal estrous activity of captive killer whales (Orcinus orca)

Abstract: To increase the basic understanding of killer whale (Orcinus orca) reproductive physiology necessary for the development of artificial breeding programs, we utilized radioimmunoassays (RIA) to detect urinary immunoreactive steroid metabolites (pregnanediol-3~-glucuronide [PdG] and estrone-conjugates [EC]) and gonadotropins (luteinizing hormone [LH] and follicle-stimulating hormone [FSH]) in urine samples from six female killer whales. Urine samples were collected from the whales by voluntary presentation beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 13 publications
3
45
0
3
Order By: Relevance
“…Christensen (1984) reported that wild north Atlantic female killer whales were pregnant at from age six to eight [25]. Additionally, Robeck et al (1993) found the first estrous cycle of six captive female killer whales from North Atlantic was 8-9 years old [26]. Our females showed similar ages for sexual maturity as described in these wild and captive female killer whales.…”
Section: Pregnancy Period Periparturient Body Temperature and Concensupporting
confidence: 73%
“…Christensen (1984) reported that wild north Atlantic female killer whales were pregnant at from age six to eight [25]. Additionally, Robeck et al (1993) found the first estrous cycle of six captive female killer whales from North Atlantic was 8-9 years old [26]. Our females showed similar ages for sexual maturity as described in these wild and captive female killer whales.…”
Section: Pregnancy Period Periparturient Body Temperature and Concensupporting
confidence: 73%
“…However, methods used in this research were also developed or in some cases evolved simultaneously from research conducted with the killer whale and bottlenose dolphin, the first two cetaceans where the development of AI was successful . As with killer whales and bottlenose dolphins, training of the Pacific white-sided dolphins for daily urine collection was required before endocrinemonitoring techniques could be applied (Walker et al 1988, Robeck et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of urinary reproductive hormones combined with ovarian ultrasound exams has resulted in describing both follicular dynamics and hormonal profiles during estrous cycles and the periovulatory period in killer whale (Walker et al 1988, Robeck et al 1993, bottlenose dolphin , and beluga . The description of the periovulatory period allowed for the development of methods for consistent prediction of ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bulk of mammalian endocrine literature reports steroid hormone levels from blood (Temte 1991, Kjeld et al 1992, Atkinson et al 1999 and to a lesser degree urine (Robeck et al 1993), feces (Rolland et al 2005(Rolland et al , 2006, and saliva (Atkinson et al 1999, Hogg et al 2005). Other sample materials from which these hormones have been extracted and measured include milk (West et al 2000), muscle (Yoshioka et al 1994), cetacean exhalant or blow (Hogg et al 2005), bone, and ocular secretions (Atkinson et al 1999).…”
Section: Introductionmentioning
confidence: 99%